Description sémantique de dans un premier temps : de la composition syntagmatique au discours - Catherine Schnedecker; Myriam Bras (Discours)
The aim of this paper is to describe the semantic behavior of the French expression dans un premier temps, known as a serial marker. We show how its meaning is partly compositional, given the importance of the temporal dimension and the constraints which this places on the nature of the constituents. We then show that dans un premier temps is “serial” in only some of its uses. In others, not reported in the literature, dans un premier temps expresses a relation of “otherness” which can be either “weak” (i.e. keeping a temporal value), or “strong” (i.e. sharply contradictory).